الأنشطة الاقتصادية بمركزي مدينة تطوان دراسة في الخصائص وإيقاعات التطور - الزروالي, بلال; أردة, إلياس (جامعة الوادي - University of Eloued, 2020)
إن الغرض من هذه الدراسة يكمن في إبراز خصائص بنية الأنشطة الاقتصادية بمركزي مدينة تطوان، وذلك من خلال التركيز على المميزات الكمية والنوعية لهذه البنية والاختلافات الحاصلة بين الحيين المدروسين، وذلك من خلال الوقوف على أهم التغيرات التي شملتهما، وتأثير ذلك على تراجع الوزن الاقتصادي بهما. وقد خلصنا في هذه الدراسة إلى أن البنية الاقتصادية لمركزي مدينة تطوان تعرف تفاوتات واختلافات جوهرية بين مختلف قطاعاتها الاقتصادية (التجارية، الخدماتية والحرفية)، إلا أن هذا الاختلاف، أحدث نوعا من التكامل والانسجام بينهما (المجالين المدروسين)؛ بل إنه لعب دورا رئيسيا في إضفاء نوع من التخصص الوظيفي The purpose of this study is to highlight the characteristics of the structure of economic activities in the two centers of Tetouan, by focusing on the quantitative and qualitative features of this structure and the differences between the two studied neighborhoods, by examining the most important changes that included them, and the effect of that on the decline of their economic weight. We concluded in this study that the economic structure of the two centers of the city of Tetouan knows fundamental differences and differences between its various economic sectors (commercial, service and crafts), but this difference resulted in a kind of integration and harmony between them (the two areas studied). Rather, it played a major role in imparting a kind of functional specialization
Economic activities in the two centers of Tetouan: a study in the characteristics and rhythms of development
مقال
Keywords: المركز العصري والمدينة العتيقة لتطوان، التخصص الوظيفي، الأنشطة الاقتصادية، الجغرافية الاقتصادية، المركزية الحضرية.